A Case Study of the Teaching Experience of Filipino and Chinese Teachers in a Chinese Elementary School - Apao, Marie Rose A.; Naparan, Genesis Balongkit (Journal of Integrated Elementary Education, 2024)
This study examined teachers' teaching experiences in an elementary school in China who engaged Chinese and Filipino students in English classes. A qualitative multiple-case study design was employed to explore teachers' experiences handling learners. Using a purposive sampling technique, data was collected from 10 teachers with experience working with students in Lam-an, Ozamiz City, Philippines. The data collection involved in-depth interviews with teachers categorized into two groups: Case 1, consisting of Filipino teachers, and Case 2, comprising Chinese teachers. The data encompassed four main categories: methods of class management in Chinese schools, student responses to classroom management, challenges faced by teachers in student management, and strategies employed by teachers to overcome these challenges. The findings revealed that teachers utilized diverse strategies to effectively instruct Chinese students, encountering challenges such as language barriers and managing a varied student body. Additionally, the teachers made efforts to understand their students better, provide necessary reinforcement to spark student interest and implement teaching strategies tailored to the needs of their students. The study concluded that while managing students in a Chinese school is challenging, witnessing students learn and grow despite these difficulties is ultimately rewarding for the teachers.